GENDER AND THE "FAITH" IN LAW: EQUALITY, SECULARISM, AND THE RISE OF THE HINDU NATION. Issue 3 (December 2020) - Kapur, Ratna
Abstract: This article analyzes how concepts of gender, gender equality, and secularism have been addressed by the higher judiciary in India in cases dealing with matters of religion. The discussion focuses on three landmark decisions of the Indian Supreme Court on gender equality. The cases involve challenges to discriminatory religious practices that target women in the Muslim-minority and Hindu-majority communities. In each case, gender equality is taken up in relation to religion in ways that produce several outcomes for women that are problematic rather than ones that are unequivocally progressive or transformative. The judicial reasoning in each case resonates with the Hindu Right's approach to gender, gender equality, and secularism. Each concept is used to advance the Hindu Right's majoritarian and ideological agenda, which seeks to establish India as a virile "Hindu" nation. Ironically, interventions by progressive groups, including feminist and human rights advocates opposed to the Hindu Right's makeover of the Indian nation, have not proved to be disruptive of gender norms; nor have they pushed back the tides of Hindu (male) majoritarianism that are increasingly determining the terms of engagement on issues of gender and faith in law.